A study of microbiological analysis and its sensitivity pattern of postoperative wound infections in obstetrics and gynecology department: retrospective study in tertiary institute in Mangalore, Karnataka, India - Shagun, Pramodha Mallik; S., Chaitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Infections acquired in hospitals are classified as nosocomial infections. Most of these infections are related to surgery, usually at the post-operative wound site. It is also termed Surgical Site Infection (SSI). Staphylococcus aureus is the documented most common organism that infect surgical wounds. This study was focused on identifying the most common microorganism documented in post-operative wound sepsis in abdomen hysterectomy surgery of obstetrics and gynaecology in a tertiary hospital in Mangalore. The aim of this study was to identify postoperative infection and to determine their current antimicrobial resistance to commonly prescribed drugs. Methods: Materials and Methods: This retrospective research was carried out in tertiary hospital with a sample size of 90 wound samples, whose records span from Jan 2014-Jan 2018. The study involved obtaining records of subjects with cases of contamination and isolation of organisms that frequently infect post-operative wound site in abdomen hysterectomy surgery. Results: A total of 79 bacterial isolates were obtained from 95 wound culture samples. In 41 cases, the isolated culture were mono microbial, 39 cultures were polymicrobial whereas no growth was obtained in 15 cases. The results showed that Staphylococcus Aureus was the most frequently isolated organism (48.1%), followed by Pseudomonas aeruginosa (18.98%) and E. coli (17.72%). Conclusions: The study is therefore important in identifying those at risk of post-operative wound sepsis and the probable causative organisms. This will be useful in the choice of prophylactic antibiotics for treatment of high-risk patients, thereby setting up an empirical antibiogram for use.